Efficacy of disitamab vedotin in non-small cell lung cancer with HER2 alterations: a multicenter, retrospective real-world study - Zhang, Meiling; Wang, Li; Wang, Qian; Yang, Jiu; Peng, Wei; Li, Xiaoyou; Shi, Meiqi; Lu, Kaihua (Frontiers in Oncology, 2024)
BackgroundNon-small cell lung cancer (NSCLC) with human epidermal growth factor receptor 2 (HER2) alterations poses a substantial treatment challenge. Current HER2-targeted therapies offer limited efficacy. Antibody-drug conjugates (ADCs) targeting HER2 have emerged as a promising therapeutic strategy. This study aimed to evaluate the clinical response to a novel ADC drug Disitamab vedotin (RC48) in advanced NSCLC with HER2 alterations.MethodsThis study conducted a retrospective review of patients harboring HER2 alterations treated with RC48 in the real world. Clinical outcomes were evaluated in terms of objective response rate (ORR), disease control rate (DCR), and progression-free survival (PFS).ResultsOut of 22 patients, 21 (95.5%) received RC48 combination therapy, while one received RC48 monotherapy. The ORR of all patients reached 45.5%, and the DCR stood at 90.9%. The median PFS (mPFS) was 7.5 months. Among patients receiving RC48 combination therapy, the ORR was 47.7%, and the mPFS of 8.1 months. The combination of RC48 with platinum+/- bevacizumab resulted in the highest ORR of 71.4% (5 out of 7 patients), with HER2 TKI following at a 50.0% ORR (4 out of 8 patients). First-line (1L) treatment with RC48 showed an ORR of 62.5% (5 out of 8 patients), second-line (2L) treatments had a 57.1% ORR (4 out of 7 patients), and beyond second-line (>2L) treatments exhibited a 14.3% ORR (1 out of 7 patients). Patients with 1L, 2L, or >2L treatment had a mPFS of 8.1 months, 7.2 months, and 7.4 months, respectively. Patients with HER2 mutations or amplifications, and those with concurrent mutations and amplifications at baseline, showed mPFS of 8.1 months, 9.4 months, and 7.4 months, respectively. The mPFS was significantly longer in patients with HER2 amplification. The most common adverse events included hand-foot syndrome (54.5%), asthenia (50.0%), decreased white blood cell count (45.5%), and liver impairment (45.5%). Grade 3 adverse events occurred in one (4.5%) patient.ConclusionRC48, particularly in combination regimens, demonstrates promising efficacy in advanced NSCLC with HER2 alterations. These findings underscore the need for further research to validate RC48’s application in clinical practice.